Exertional heat fatalities in Australian sport and recreation. Issue 8 (August 2021) - Fortington, Lauren; Gamage, Prasanna; Cartwright, Anna; Bugeja, Lyndal
Abstract: Objectives: To describe the number and case characteristics of sport and recreation-related exertional heat deaths in Australia and summarise recommendations derived from case narratives. Design: Descriptive, population-based, retrospective cohort study. Methods: Cases were identified using the National Coronial Information System (NCIS) through multiple search strategies comprising queries, keywords and cause of death codes. Cases were included where there was evidence that the deceased was actively engaged in sport or recreation and exertional heat illness was causal or contributory to the death. Data extraction were performed independently, in duplicate, to ensure accuracy. Descriptive statistics are used to report deceased's socio-demographic characteristics, incident characteristics, type of sport/recreational activity and time sequence of events. Content analysis is used to summarise recommendations. Results: Thirty-eight deaths (males n = 29, 74%; median age = 40 years, range 8–77) were identified during the study period (2001 to 2018), with 22 recommendations for five cases. Two cases occurred during organised sport and 36 during active recreation, of which 27 were in hiking. Eleven (29%) individuals were international visitors. There were 22 recommendations across 5 cases presented, with a focus on education and training. Conclusions: Exertional heat deaths in outdoor recreation in Australia were far more prevalent than cases in organised sport. The largest proportion of deaths occurred in hiking with two populations featuring: males aged 15–45 years and international visitors. Considering the incident characteristics and time sequence of events, measures such as early recognition of symptoms, provision of first aid and timely access to emergency medical care are important to prevent fatalities.